Vision Steered Beam-forming and Transaural Rendering for the Artificial Life Interactive Video Environment, (ALIVE) - Casey, Michael A.; Gardner, William G.; Basu, Sumit (Proceedings of the Audio Engineering Society 99th Conference (AES '95). New York, New York., 1995)
This paper describes the audio component of a virtual reality system that uses remote sensing to free the user from body-mounted tracking equipment. Position information is obtained from a camera and used to constrain a beam-forming microphone array, for far-field speech input, and a two-speaker transaural audio system for rendering 3D audio.